2022
DOI: 10.1002/anie.202205183
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Photoluminescent Single‐Chain Nanoparticles by Electrostatic‐Mediated Intramolecular Crosslinking

Abstract: We report the large‐scale synthesis of photoluminescent single‐chain nanoparticles (SCNPs) by electrostatic‐mediated intramolecular crosslinking in a concentrated solution of 40 mg mL−1 by continuous addition of the free radical initiator. Poly(vinyl benzyl chloride) was charged by quaternization with vinyl‐imidazolium for the intramolecular crosslinking by using 2,2‐dimethoxy‐2‐phenylacetophenone (DMAP) as the radical initiator. Under the electrostatic repulsion thus interchain isolation, the intrachain cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Inspired by the intricate three-dimensional (3D) folding observed in natural proteins, single-chain nanoparticles (SCNPs) have emerged as a prominent focus in chemistry and nanoscience. These SCNPs are nanostructures formed through the intramolecular cross-linking or collapsing of individual polymer chains. As a new type of soft nanomaterial, SCNPs exhibit diverse characteristics that make them suitable for various fields, such as in catalysis, biomedical applications, and optical materials. Beyond their diverse applications, an ultimate goal is to mimic the folding patterns found in biomacromolecules, such as proteins, into well-defined 3D-folded structures to understand their associated functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the intricate three-dimensional (3D) folding observed in natural proteins, single-chain nanoparticles (SCNPs) have emerged as a prominent focus in chemistry and nanoscience. These SCNPs are nanostructures formed through the intramolecular cross-linking or collapsing of individual polymer chains. As a new type of soft nanomaterial, SCNPs exhibit diverse characteristics that make them suitable for various fields, such as in catalysis, biomedical applications, and optical materials. Beyond their diverse applications, an ultimate goal is to mimic the folding patterns found in biomacromolecules, such as proteins, into well-defined 3D-folded structures to understand their associated functions.…”
Section: Introductionmentioning
confidence: 99%
“…Such a strategy was also proven to be efficient by Diesendruck later on for the synthesis of poly­[(PMMA)- co -AEMA]-based SCNPs in five different solvents. More recently, the Yang group demonstrated that adding 25% ether, a poor solvent, to the polymer solution before electrostatic-mediated intrachain cross-linking can further reduce the size of the obtained SCNPs. However, their results demonstrate that adding 50% ether leads to interchain cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic interaction along the crosslinkable block plays the key role in providing a long-range protection, thus ensuring the exclusive intramolecular crosslinking in concentrated solutions. Both the introduction of electrostatic interaction and intramolecular crosslinking are readily achieved by either covalent bonding or physical complexation. Along with this protocol, an example Janus polymer/polymer colloidal dimer has been synthesized by subsequential crosslinking of the diblock copolymer of poly­(isoprene)- block -poly­(vinylpyridine) (PI- b -P4VP) at an unprecedented high concentration of 100 mg/mL . The PI block is modified with 2-mercaptoethylamine hydrochloride and crosslinked with 1,6-hexanediisothiocyanate, and the P4VP block is modified with iodoethane and crosslinked with 1,5-diiodopentane.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vivo accumulation of large particles in the body is a known critical point. For this reason, since their infancy, the so-called single-chain polymer nanoparticles (SCNPs) were endowed with fluorescent features, , and their self-assembly in aqueous solutions was investigated in view of their potential use as fluorescent probes and carriers of therapeutics agents with improved biodistribution . Indeed, SCNPs are a convenient tool to obtain soft nanomaterials exploiting the folding of single polymer chains, via covalent or non-covalent intramolecular interactions.…”
Section: Introductionmentioning
confidence: 99%